BUDAYA WAROK PONORAGAN: MEDIA PENGUATAN WAWASAN KEBANGSAAN MASYARAKAT PONOROGO - ROFIQ, ARIF (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
This research aims to represent the socio-cultural community of Ponorogo as a medium for strengthening national insight. This research is descriptive research using a qualitative approach. In this research, qualitative data was obtained through interviews with research informants and field observations, namely the Ponorogo Reyog Culture which is growing in all sub-districts throughout Ponorogo Regency. Data collection techniques use interviews and observation. Data analysis techniques include Data collection, Data condensation, Data display, and Conclusion drawing/verification. The research results show that the Ponorogo Reyog Culture plays a very important role in strengthening the unity and integrity of the Ponorogo community. This can be seen from the way the community is actively involved in maintaining and preserving this tradition. Apart from that, Ponorogo Reyog Culture has also succeeded in becoming a proud cultural identity for the local community, so that it can become a cultural tourism attraction that can improve the local economy in Ponorogo Regency. Thus, this research provides a significant contribution in understanding the importance of local culture as part of the nation's wealth that must be preserved and maintained. Suggestions for further research are to involve more elements of society in efforts to preserve Reyog Ponorogo culture, as well as dig deeper into the cultural tourism potential of Ponorogo Regency. In this way, it is hoped that it can continue to increase people's awareness and pride in their cultural heritage, so that it can continue to be maintained and preserved for future generations. ABSTRAKPenelitian ini bertujuan untuk representasi sosial cultural masyarakat Ponorogo sebagai media penguatan wawasan kebangsaan. Penelitian ini merupakan penelitian deskriptif dengan menggunakan pendekatan kualitatif. Dalam penelitian ini, data kualitatif diperoleh melalui wawancara dengan informan penelitian dan observasi lapangan yaitu Budaya Reyog Ponorogo yang tumbuh berkembang di seluruh kecamatan Se-Kabupaten Ponorogo. Teknik pengumpulan data menggunakan wawancara dan observasi. Teknik analisis data meliputi Data collection, Data condensation, Data display, dan Conclusion drawing/ verification. Hasil penelitian menunjukkan bahwa Budaya Reyog Ponorogo memainkan peran yang sangat penting dalam memperkuat kesatuan dan persatuan masyarakat Ponorogo. Hal ini terlihat dari cara masyarakat secara aktif terlibat dalam mempertahankan dan melestarikan tradisi ini. Selain itu, Budaya Reyog Ponorogo juga berhasil menjadi identitas budaya yang membanggakan bagi masyarakat setempat, sehingga dapat menjadi salah satu daya tarik wisata budaya yang dapat meningkatkan ekonomi lokal di Kabupaten Ponorogo. Dengan demikian, penelitian ini memberikan kontribusi yang signifikan dalam memahami pentingnya budaya lokal sebagai bagian dari kekayaan bangsa yang harus dilestarikan dan dijaga. Saran untuk penelitian selanjutnya adalah melibatkan lebih banyak elemen masyarakat dalam upaya pelestarian budaya Reyog Ponorogo, serta menggali lebih dalam potensi wisata budaya yang dimiliki oleh Kabupaten Ponorogo. Dengan demikian, diharapkan dapat terus meningkatkan kesadaran dan kebanggaan masyarakat terhadap warisan budaya yang dimiliki, sehingga dapat terus terjaga dan dilestarikan untuk generasi mendatang.